Knowledge discovery in sport - Fister, I.; Fister Jr., I.; Fister, D. (Computational intelligence in sports, 2018)
The chapter deals with knowledge discovery from data in sport. In the narrower sense, knowledge discovery from data refers to a data mining that also incorporates methods from other domains, like statistics, pattern recognition, machine learning, visualization, association rule mining and computational intelligence algorithms.